The Role of Change Agents in Integrated Marketing Communications Development of A Conceptual Framework - Selvarajan, P.; Safna, M.I.N. (Faculty of Graduate Studies, University of Sri Jayewardenepura, 2019)
The aim of this study is to examine various roles played by change agents in Integrated Marketing Communications (IMC) and to develop a model to show the relationship between the roles of change agents and IMC. Literature revealed that change agents play immense role in promoting change among the consumers through effective communication. Further, they act as role models in initiating, managing or implementing change on the attitudes, personalities and perceptions of buyers. As one single marketing tool is not much effective to achieve marketing communication process, the IMC is used as a holistic approach by organisations to promote their brands across multiple marketing communication mix. In the current era, the change agents are moving towards IMC and playing numerous roles to implement changes among their targeted consumers and retain them as customers in long run. Since the marketing is crucial in the digital world, the roles played by them should also be dynamic. Therefore, this research study investigated various roles of change agents in IMC by using the methods of reviewing of related literature and observing the marketing practices of well-known industries in Sri Lanka to derive the findings. Further, this present study attempts to develop and recommend a conceptual model which shows various roles of change agents in IMC in various organisational settings. Moreover, the findings also illustrate that change agents play vital roles as “Investigator”, “Advocate”, “Encourager”, “Mediator”, “Convincer” and “Manager” in IMC at any type of marketing organisations. Therefore, researchers conclude that the change agents play the above roles in IMC functions for a successful marketing. It is believed that further research could be extended by adopting this model in either qualitative or quantitative research in future.
Keywords: Advocate; change agents; Convincer; Integrated marketing communications; Mediator